Transapical tricuspid valve‐in‐ring implantation: An alternative approach to a challenging clinical scenario. Issue 5 (12th August 2016) - Girdauskas, Evaldas; Lauer, Bernward; Kuntze, Thomas
Abstract : We report on a transapical tricuspid valve‐in‐ring implantation performed via right ventricular apex using the Sapien‐XT‐prosthesis. A 57‐year‐old woman with recurrent episodes of right heart failure and three previous sternotomies, including tricuspid valve repair with a 32 mm Carpentier–Edwards–Classic annuloplasty ring was admitted due to recurrent severe tricuspid regurgitation. Given the excessive surgical risk, a 29 mm Sapien‐XT‐prosthesis was selected for valve‐in‐ring implantation. Transapical valve‐in‐ring implantation procedure was uneventful. Predischarge echocardiography showed only trace paravalvular tricuspid regurgitation in the septal region. Transapical approach via right ventricular apex is a viable alternative for tricuspid valve‐in‐ring implantation in selected high‐risk patients. © 2016 Wiley Periodicals, Inc.